Pathogenic Detection by Metagenomic Next-Generation Sequencing in Osteoarticular Infections - Huang, Zi-da; Zhang, Zi-jie; Yang, Bin; Li, Wen-bo; Zhang, Chong-jing; Fang, Xin-yu; Zhang, Chao-fan; Zhang, Wen-ming; Lin, Jian-hua (Frontiers in Cellular and Infection Microbiology, 2020)
Objectives: To evaluate metagenomic next-generation sequencing (mNGS) as a diagnostic tool in detecting pathogens from osteoarticular infection (OAI) samples. Methods: 130 samples of joint fluid, sonicate fluid, and tissue were prospectively collected from 92 patients with OAI. The performance of mNGS and microbiology culture was compared pairwise. Results: The overall sensitivity of mNGS was 88.5% (115/130), significantly higher than that of microbiological culture, which had a sensitivity of 69.2% (90/130, p < 0.01). Sensitivity was significantly higher for joint fluid (mNGS: 86.7% vs. microbiology culture: 68.7%, p < 0.01) and sonicate fluid (mNGS: 100% vs. microbiology culture: 66.7%, p < 0.05) samples. mNGS detected 12 pathogenic strains undetected by microbiological culture. Additional pathogens detected by mNGS were Coagulase-negative Staphylococci, Gram-negative Bacillus, Streptococci, Anaerobe, non-tuberculosis mycobacterium, MTCP (p > 0.05), and Mycoplasma (OR = ∞, 95% confidence interval, 5.12–∞, p < 0.001). Additionally, sensitivity by mNGS was higher in antibiotic-treated samples compared to microbiological culture (89.7 vs. 61.5%, p < 0.01). Conclusions: mNGS is a robust diagnostic tool for pathogenic detection in samples from OAI patients, compared to routine cultures. The mNGS technique is particularly valuable to diagnose pathogens that are difficult to be cultured, or to test samples from patients previously treated with antibiotics.